Political use and consequences of sport events - Rybka, Pauline Johanna; Němec, Jan, 1980 srpen 23.-; Kuta, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
In the theory part of this thesis will examine the connection between politics and sport, including the politicization of major sport events and the particular role of non-democratic states as host nations. In the empirical part, three case studies (Summer Olympics Beijing 2008, Winter Olympics Sochi 2014, and FIFA World Cup Qatar 2018) will be analyzed in the light of how they have influenced (or have the potential to influence) reforms, the adoption of democratic structures, and the human rights situation.
Vedoucí práce: Jan Němec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses